Answer:
Step-by-step explanation:
Step 1: We must locate the slope, by using the slope formula, which is:
[tex]\frac{y2-y1}{x2-x1}[/tex]
When we plug it in we get:
[tex]\frac{-2-10}{9-3}[/tex]
Which simplifies to a -2
Step 2: We must plug in our values in the point-slope formula which is:
[tex]y-y1=m(x-x1)[/tex]
We can plug in (3,10) or (9,-2). It doesn't matter which one, we'll end up with the same answer. For this example, we'll use (3,10)
When we plug in our values we will get:
[tex]y-10=-2(x-3)[/tex]
Step 3: Now we just need to put our equation in slope-intercept form
[tex]y-10=-2(x-3)[/tex]
[tex]y-10=-2x+6\\y=-2x+16[/tex]
Therefore, our answer is [tex]y=-2x+16[/tex]
Hope this helps!!!